La memoria no es "cosa del pasado". Los retos de la memoria en Colombia desde una perspectiva filosófica (2019)
ABSTRACT: The dissociation that we use to establish between present and past, as well as between experience and remembrance, leads to major dilemmas for those who try to make memory. This article reveals the implications and limitations of the assumption that memory “starts” when a chapter of history has been “closed”. In contrast to this view, and by means of Walter Benjamin’s concept of “remembrance” (Eingedenken), we will present the conception of a productive, critical, and dynamic memory, where times will coalesce and be inverted. The challenge with which Colombia has to confront itself results precisely from this premise: memory is not a “matter of the past”, since the past is not dissociated from the present.